2021
DOI: 10.36660/ijcs.20200290
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cutoff of the TG/HDL-c ratio for Cardiovascular Risk in Hypertensive and Diabetic Patients Monitored by Primary Health Care in a city in Minas Gerais

Abstract: Currently, cardiovascular diseases (CVD) are one of the most important public health problems in the world and one of the main causes of prolonged hospitalization and health expenditures in Brazil. 1,2 Among CVD, coronary artery disease (CAD) stands out as the leading cause of death in Brazil 3,4 and worldwide. 3 Dyslipidemias are related to the development of atherosclerosis and, consequently, CAD. 5 Early detection of individual cardiovascular risk (CVR) is important to prevent CVD, 1,5,6 define therapy 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Exams showed that the cut-off values of the ratio TG/HDL that reflect the cardiovascular risks were ≥ 3.26 for men and ≥ 2.72 for women. [16] The data suggest that TG/HDL is a marker of increased atherosclerotic extension in prediabetes and newly diagnosed T2DM and may be useful to identify subjects with a higher cardiovascular risk profile. TG/HDL-C was associated with insulin resistance in Chinese patients with newly diagnosed T2DM (r = 0.21, P<0.01).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Exams showed that the cut-off values of the ratio TG/HDL that reflect the cardiovascular risks were ≥ 3.26 for men and ≥ 2.72 for women. [16] The data suggest that TG/HDL is a marker of increased atherosclerotic extension in prediabetes and newly diagnosed T2DM and may be useful to identify subjects with a higher cardiovascular risk profile. TG/HDL-C was associated with insulin resistance in Chinese patients with newly diagnosed T2DM (r = 0.21, P<0.01).…”
Section: Discussionmentioning
confidence: 92%
“…In the current edition of the International Journal of Cardiovascular Sciences, Silva et al, [16] evaluated 833 individuals, of whom 62.8% were women, with an the average age of 62 years, with high blood pressure and/or diabetes, who received medical care at the Family Health Unit in the city of Viçosa, Minas Gerais, Brazil. Exams showed that the cut-off values of the ratio TG/HDL that reflect the cardiovascular risks were ≥ 3.26 for men and ≥ 2.72 for women.…”
Section: Discussionmentioning
confidence: 99%
“…A clearcut, straight correlation was observed between the TG/HDL index and the LS summation. However, it is necessary to point out that the cutoffs of the TG/HDL ratio have not been universally established, as the index varies significantly according to gender, body mass index, insulin resistance, ethnicity, comorbidities, and other determinants [ 64 , 65 , 66 , 67 , 68 ]. Despite certain correspondence between both scales, intermediate-risk categories had considerable overlap.…”
Section: Discussionmentioning
confidence: 99%